2022
DOI: 10.3389/fphar.2022.829394
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of Sodium Bicarbonate Ringer’s Solution in Critically Ill Patients: A Retrospective Cohort Study

Abstract: Background: Sodium bicarbonate Ringer’s solution has been widely used in clinical practice in recent years. There are few clinical studies on the efficacy and safety of this fluid among critically ill patients until now.Method: This retrospective cohort study included critically ill adult patients in the intensive care unit (ICU) of Tongji Hospital from 1 January 2019 to 31 December 2020. By reviewing exclusively the use of either sodium bicarbonate Ringer’s solution or saline for resuscitation or maintenance,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…We also found an improvement in the minor complications in the BRS group like reducing the incidence of wound bleeding and impaired liver function. It indicates that BRS can alleviate liver function metabolic burden and inhibit the aggravation of coagulation dysfunction to a certain extent during uid therapy [29]. Study by Su et al showed that LRS can cause granulocyte respiration bursts, aggravate systemic in ammations and then increase the capillary permeability and aggravate the tissue edema [30].…”
Section: Discussionmentioning
confidence: 99%
“…We also found an improvement in the minor complications in the BRS group like reducing the incidence of wound bleeding and impaired liver function. It indicates that BRS can alleviate liver function metabolic burden and inhibit the aggravation of coagulation dysfunction to a certain extent during uid therapy [29]. Study by Su et al showed that LRS can cause granulocyte respiration bursts, aggravate systemic in ammations and then increase the capillary permeability and aggravate the tissue edema [30].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, for liver transplant patients, intraoperative input of LRS will increase liver and kidney load and is not an ideal crystal solution. BRS is a physiological alkaline buffer with HCO 3 , which is a direct alkaline effect by binding with H + to quickly correct the acidosis and maintain acid-base balance [ 21 , 22 ]. BRS is a new type of balanced crystal buffered by bicarbonate rather than organic anions, in which case it may perform better at preserving the acid-base state [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…[creatinine = 0.74 − 0.2 (if female) + 0.08 (if African American) + 0.003 × age (in years)]. If a patient had documented CKD, it was defined as the lowest creatinine value during hospitalization [ 6 , 9 , 24 , 25 ]. Baseline glomerular filtration rates were calculated using the Modification of Diet in takes diseases equation estimation [ 26 ].…”
Section: Methodsmentioning
confidence: 99%